Perbedaan Obat Berdasarkan Nama Generik dan Nama Dagang pada Masyarakat Desa Genteng Kulon - Dita Amanda Deviani; Stephanie Devi Artemisia; Azmi Prasasti; Titis Sriyanti; Nina Wijiani; Riyan Dwi Prasetyawan; Abi Mas Udianto; Sari Prayudeni; Ima Fitria Lestari; Nur Hidayati; Anung Kustriyani (Jurnal Pengabdian Masyarakat (JUDIMAS), 2024)
Drugs are substances, guide substances, and biological products that are used to influence or investigate physiological systems or pathological states. Medicines can have generic names and trade names. People think that drugs with generic names produce lower therapeutic effects than trade names, as is the case in the Genteng Kulon community. The aim of this community service activity is to provide information regarding the differences between medicines based on generic names and trade names to the Genteng Kulon Village community. The method used was counseling and giving leaflets. Apart from that, people also do pre-test and post-test questions. This community service activity was attended by 50 representatives of posyandu figures in Genteng Kulon Village. The result of community service activities is that representatives of posyandu figures receive information regarding the differences in medicines based on generic names and trade names. People can use drugs with generic names without worrying about efficacy, especially for people who receive drug services from BPJS. There is an increase in the post test score compared to the pre test.